Lessing und das Judentum: Lektüren, Dialoge, Kontroversen im 20. und 21. Jahrhundert - Berghahn, Cord-Friedrich; Niefanger, Dirk; Och, Gunnar; Siwczyk, Birka (Kamenzer Lessing-Studien, 2021)
The essays in this volume document the last of three international and interdisciplinary conferences on the theme of "Lessing and Judaism". The focus is on the 20th century, a particularly volatile period for the reception of Lessing's work, in which the upheavals of the time, ideological tensions and controversies, and above all the rupture of civilisation that was the Shoah, left deep traces. The spectrum of philological, literary, cultural, philosophical, historical and media-related studies shows how engagement with Lessing has been pluralised and polarised against the background of antisemitism and Jewish self-determination, but also in the context of non-Jewish repression and grief. Together with the first volume, published in 2015, which examined the same theme in the context of the 18th and 19th centuries, this forms a stimulating compendium, with a wide range of perspectives, for researchers and for anyone interested in Lessing's contemporary relevance